Factors associated with playing football after anterior cruciate ligament reconstruction in female football players - Fältström, A.; Hägglund, M.; Kvist, J. (Scandinavian Journal of Medicine & Science in Sports, 2016)
This study investigated whether player-related factors (demographic, personality, or psychological factors) or the characteristics of the anterior cruciate ligament (ACL) injury were associated with the return to playing football in females after ACL reconstruction (ACLR). We also compared current knee function, knee related quality of life and readiness to return to sport between females who returned to football and those who had not returned. Females who sustained a primary ACL rupture while playing football and underwent ACLR 6-36 months ago were eligible. Of the 460 contacted, 274 (60%) completed a battery of questionnaires, and 182 were included a median of 18 months (IQR 13) after ACLR. Of these, 94 (52%) returned to football and were currently playing, and 88 (48%) had not returned. Multiple logistic regression analysis identified two factors associated with returning to football: short time between injury and ACLR (0-3 months, OR 5.6; 3-12 months OR 4.7 vs reference group > 12 months) and high motivation. Current players showed higher ratings for current knee function, knee-related quality of life, and psychological readiness to return to sport (P < 0.001). Undergoing ACLR sooner after injury and high motivation to return to sports may impact a player's return to football after ACLR.